Resistin upregulates fatty acid oxidation in synoviocytes of metabolic syndrome-associated knee osteoarthritis via CAP1/PKA/CREB to promote inflammation and catabolism - Lu Ding; Jin-Yi Ren; Yi-Fan Huang; Jian-Zeng Zhang; Zi-Ran Bai; Yi Leng; Jun-Wei Tian; Jing Wei; Min-Li Jin; Guan Wang; Xia Li; Xin Qi (Arthritis Research & Therapy)
Abstract Background Metabolic Syndrome (MetS), as a syndrome characterized by low-grade inflammation and energy metabolism disorders, is considered to be an important systemic risk factor for knee osteoarthritis (KOA). Our previous study showed that the protein level of serum resistin was positively correlated with the degree of metabolic disorder in MetS-OA. However, whether Resistin promotes the progression of KOA synovitis and the underlying mechanisms remain unclear. This study mainly investigateswhether there were metabolism disorder which promote inflammatory and catabolic phenotype in fibroblast-like synoviocytes (FLS) from KOA patients with MetS (MetS-KOA-FLS), and the roles and mechanisim of resistin in MetS-KOA-FLS. Methods Comparative analysis of synovium and FLS from MetS-associated KOA (MetS-KOA) and non-MetS-associated KOA (nMetS-KOA) of females to detect the differences in inflammation, catabolism and glycolipid metabolism. Serum from MetS-KOA stimulated nMetS-KOA-FLS to detect the effect of MetS microenvironment on inflammation, catabolism and glycolipid metabolism of nMetS-KOA-FLS. Resistin stimulated MetS-KOA-FLS to explore the effect of resistin on inflammation and catabolism of MetS-KOA-FLS and its specific mechanism. Results Compared with nMetS-KOA-FLS, MetS-KOA-FLS expressed higher inflammatory related factors, catabolic enzymes, and showed stronger adhesive and invasive ability. Resistin was found to be an important factor in the serum and internal environment of MetS-KOA patients, and it mediated the differences in fatty acid oxidation (FAO) between the two groups. Resistin activated the PKA/CREB pathway through CAP1 and upregulated FAO, promoting the inflammatory and catabolic phenotype of MetS-KOA-FLS. Conclusions This study clarifies the mechanism by which MetS causes synovitis from a metabolic perspective and provides new ideas for further research and treatment of MetS-KOA.